2014
DOI: 10.3391/mbi.2014.5.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Small boats provide connectivity for nonindigenous marine species between a highly invaded international port and nearby coastal harbors

Abstract: Stemming from a recent freshwater invasives conference, Caffrey et al. (2014) identified 'the top 20 issues' that relate to invasive alien species (IAS) management in Europe. With a view to complement and balance the issues highlighted in their account, we offer six important additions that relate to the marine environment. These are: preventive measures, concerns of loss of taxonomic expertise and species identity, gaps in the knowledge of certain taxa and regions, inconsistencies of terminology, need for val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 33 publications
1
63
0
Order By: Relevance
“…These may have arrived with intraregional small craft-fishing boats, which travel between harbours and smaller embayments (Wasson et al 2001;Zabin et al 2014).…”
Section: Fishing Boatsmentioning
confidence: 99%
“…These may have arrived with intraregional small craft-fishing boats, which travel between harbours and smaller embayments (Wasson et al 2001;Zabin et al 2014).…”
Section: Fishing Boatsmentioning
confidence: 99%
“…There is, however, growing recognition of the role of recreational vessels 39 as vectors of non indigenous species Clarke Murray et al, 2011;Minchin et al, 2006), and recent studies have revealed the significant risk of secondary introductions in stepping stone invasions (e.g. Burgin and Hardiman, 2011; in marine environments (Zabin et al, 2014). In Australia, most commercial and recre-ational vessels are not required to inspect their hulls for non indigenous species upon first entry in Australian waters or for travel domestically within Australia.…”
mentioning
confidence: 99%
“…Studies of international and domestic recreational boats have demonstrated a range of fouling rates, with most surveys showing 84 that over 50% of vessels, and sometimes as high as 80%, having some level of fouling Lacoursière-Roussel et al, 2012b;Minchin et al, 2006;Zabin et al, 2014). The extent of fouling on any individual vessel, how-87 ever, is often highly variable, irrespective of sample sizes and methodology Brine et al, 2013;Clarke Murray et al, 2011;.…”
mentioning
confidence: 99%
See 2 more Smart Citations